Clinico-pathological correlation of abdominal lymphadenopathy - Ramole, Yashpal; Tekam, Vijay (International Surgery Journal, 2018)
Background: This study “clinico-pathological correlation of abdominal lymphadenopathy" intended to know the various etiological causes behind the abdominal lymphadenopathy and different modes of presentation which can help in treatment and prognosis in our setup which helps in better management of these cases thus helping to improve prognosis. Methods: The" Clinico-Pathological Correlation of Abdominal Lymphadenopathy is a clinical study of 250 consecutive cases of abdominal Lymphadenopathy which were found during intraoperative laparotomy in Hamidia Hospital (Gandhi Medical College), Bhopal. This is observational study will be carried out in the Department of Surgery, Gandhi Medical College. Total 250 consecutive cases will be included in this study having per-operative findings of lymphadenopathy, where laparotomy will be done for various regions. Prior to surgery thorough history will be taken and meticulous physical examination will be performed. Necessary laboratory and imaging studies shall do to establish the diagnosis. Results: Tuberculosis is one of the common causes of Abdomen lymphadenopathy. Age incidence more in males and in second and third decade of life is more common. Abdominal pain, loss of weight and appetite with bowel disturbances are the common clinical manifestation. It is obvious from this study that tuberculosis is a problem in our country. Regarding the abdominal tuberculosis, the diagnostic problem persists for those patients where pulmonary tuberculosis is not obvious. Most tubercular patients present with perforation peritonitis. Conclusions: This study support fact that abdominal lymphadenopathy is important indicator of underlying cause of pathogenesis from which we reach the diagnosis. In present study in 10% cases only lymph nodes are positive for tuberculosis without tissue diagnosis, which can be treated to prevent the further complications.